Evaluation of Non-communicable Diseases’ Drug Home Delivery Project during the COVID-19 Outbreak in Sila Lat District, Si Sa Ket Province - Asipong, Somjit; Pensirinapa, Nittaya (Journal of Health Sciences and Wellness, 2023)
This research aimed (1) to evaluate the results of the Non-communicable Diseases’ (NCDs) Drug Home Delivery Project on context, inputs and processes from service providers’ perspective, (2) to compare the appropriateness scores for the project implementation of providers within and outside the Primary Care Unit (PCU) of Sila Lat Hospital, (3) to assess the project performance regarding receiving the drug and satisfaction of service recipients, and (4) to compare the satisfaction levels of the service recipients between the groups who received the drug before an appointment and without appointment and between inside and outside the PCU area of Sila Lat Hospital in Si Sa Ket province. The design of the paper was a survey study to assess the home-based non-communicable disease drug delivery project. The first group of samples was 6 service providers who were responsible for chronic non-communicable diseases in sub-district health-promoting hospitals (outside the PCU area) and in the PCU area of ​​Silalad Hospital by purposive sampling and volunteers/caregivers by simple random sampling of 50% selection of 1 person per village out of 44 villages. The second group was the 100 service recipients who had their medicines delivered at home from June 2020 to November 2021, selected the simple random sampling from those who returned for treatment at Sila lat Hospital after the better COVID-19 situation. Data were collected in May–June 2022 using two questionnaires – one for service providers and the other for service recipients, whose reliability values were 0.91 and 0.81, respectively. Statistical analysis was carried out using descriptive statistics, independent t-test, and Mann Whitney U test. The results showed that evaluation of the project service provider had the average scores in each aspect and overall were at a high level. The average score of the appropriateness of the project implementation of service providers in the PCU area (context, 22.30±2.06 input 12.73±1.74 Process 16.55±2.46 and overall 51.64±4.74) was higher than outside PCU area Sila lat Hospital (context 19.23±3.20, input 11.23±1.91 process 14.85±2.57 and overall 45.31±2.27) When comparing the scores, it was found that the context input and overall factors were different at the level of statistical significance of 0.05 (p-value = 0.006, 0.030 and 0.009). However, no difference was found for in the process score. For the drug receiving evaluation, the recipients in the PCU area received the drug before the appointment at a higher proportion compared with those outside the PCU area (58.50% and 33.90%, respectively).Their overall satisfaction was at the highest level. In addition comparing the service recipients’ satisfaction between the group receiving drugs before the appointment and without an appointment, and between inside and outside the PCU area had no significant difference in the satisfaction scores.